2019
DOI: 10.1002/aic.16797
|View full text |Cite
|
Sign up to set email alerts
|

Recovery rheology via rheo‐SANS: Application to step strains under out‐of‐equilibrium conditions

Abstract: Stress relaxation from a step strain test provides important information about constituent dynamics, but if a material has experienced a complex shear history, the underlying physics is not straightforward to access. We use recovery rheology and rheo‐small‐angle neutron scattering to probe the nonlinear dynamics of an entangled wormlike micelle solution by applying step strains after complex shear histories enforced by large‐amplitude oscillatory shear (LAOS) flow. We show that a universal relaxation modulus c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 78 publications
0
4
0
Order By: Relevance
“…Recently, scattering coupled with in situ rheological measurements has become more popular to aid in the development of structure–property relationships. Rheo-small-angle-neutron scattering (rheo-SANS, Figure ) is most common in polymer networks due to the contrast selectivity as mentioned for static SANS, and it provides a direct correlation between the structure and the macroscopic rheological response. There are a number of flow devices compatible with in situ neutron scattering measurements (flow-SANS or rheo-SANS), most notably, Couette cells, capillary flow cells, 1–2 shear cells, and even entire oscillatory rheometers .…”
Section: Network Structurementioning
confidence: 99%
See 2 more Smart Citations
“…Recently, scattering coupled with in situ rheological measurements has become more popular to aid in the development of structure–property relationships. Rheo-small-angle-neutron scattering (rheo-SANS, Figure ) is most common in polymer networks due to the contrast selectivity as mentioned for static SANS, and it provides a direct correlation between the structure and the macroscopic rheological response. There are a number of flow devices compatible with in situ neutron scattering measurements (flow-SANS or rheo-SANS), most notably, Couette cells, capillary flow cells, 1–2 shear cells, and even entire oscillatory rheometers .…”
Section: Network Structurementioning
confidence: 99%
“…Capillary and microfluidic flow devices, , for low sample volume experiments under arbitrary deformation fields, are also available. Such rheo-SANS experiments have given insights into the interplay of chain branching and alignment with the formation/breakage of reversible cross-links under different shear conditions. Further, rheo-SAXS has shown that the glassy styrene domains (within a microphase-separated poly­(styrene- b -ethylene- co -butylene- b -styrene) (SEBS) triblock thermoplastic elastomer) change shape, spacing, and ordering while undergoing uniaxial or biaxial stretching …”
Section: Network Structurementioning
confidence: 99%
See 1 more Smart Citation
“…However, there are weaknesses in this approach due to the challenge of interpreting the physical meaning of these higher-order harmonics in the context of molecular deformations. Recently, a class of methods known as “recovery rheology” approaches have sought to specifically overcome this limitation. Here, oscillatory shear is abruptly “stopped” mid-deformation, and the relaxation of the material to the applied shear is also measured. This enables the extraction of molecular relaxation processes and has been applied to a number of material classes including linear polymer solutions and melts , and colloidal yield-stress fluids .…”
Section: Outlook: Bottlebrush Polymers As a Materials Design Platformmentioning
confidence: 99%